2008
DOI: 10.4269/ajtmh.2008.79.899
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Rickettsia rickettsii Isolated from Human Clinical Samples and from the Rabbit Tick Haemaphysalis leporispalustris Collected at Different Geographic Zones in Costa Rica

Abstract: Five strains of spotted fever group (SFG) rickettsiae previously isolated from human clinical cases and from the tick Haemaphysalis leporispalustris were used for molecular characterization in this study to establish their genetic relationship compared with the prototype Rickettsia rickettsii strain Sheila Smith. Samples were tested by polymerase chain reaction (PCR) targeting the rickettsial genes gtlA, ompA, and ompB. PCR products of the latter two genes were DNA sequenced and compared with available sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
1
11
0
6
Order By: Relevance
“…35,36 Limited genetic analyses of a Costa Rica Hlp isolate reveals complete identity with several United States isolates of R. rickettsii, including the Hlp #2 and Sheila Smith strains. 37 Collectively, these data reinforce the observation that the severity of disease caused by a particular strain of R. rickettsii in a non-human host cannot be extrapolated routinely to the severity of disease in a human host, 7,9,15,34,38 and that additional molecular analyses are needed to better elucidate genetic determinants of virulence in R. rickettsii.…”
Section: Discussionsupporting
confidence: 65%
“…35,36 Limited genetic analyses of a Costa Rica Hlp isolate reveals complete identity with several United States isolates of R. rickettsii, including the Hlp #2 and Sheila Smith strains. 37 Collectively, these data reinforce the observation that the severity of disease caused by a particular strain of R. rickettsii in a non-human host cannot be extrapolated routinely to the severity of disease in a human host, 7,9,15,34,38 and that additional molecular analyses are needed to better elucidate genetic determinants of virulence in R. rickettsii.…”
Section: Discussionsupporting
confidence: 65%
“…For example, R. rickettsii infection can be acquired in Canada and Mexico, as well as in Central America and South America, where cases are reported from Costa Rica, Panama, Brazil, Colombia, and Argentina (253)(254)(255)(256)(257)(258)(259)(260). R. parkeri infections have been described in Uruguay, Brazil, and Argentina (38,253,261,262).…”
Section: Travel Outside Of the United Statesmentioning
confidence: 99%
“…1). Interestingly, while low-, mild-, and high-virulent strains of R. rickettsii have been reported in the eastern and western parts of the United States (20,22), only highvirulent strains, responsible for high fatality rates, have been reported in Central/South America, regardless of the tick vector (2,(23)(24)(25)(26)(27)(28)(29). While our results of no polymorphisms among Central/ South American isolates was biased because most of these isolates were derived from fatal cases, a recent study reported the same clade distribution as shown in our Fig.…”
mentioning
confidence: 99%